The identical-path truck platooning problem. (March 2018) - Boysen, Nils; Briskorn, Dirk; Schwerdfeger, Stefan
Highlights: This paper investigates the platooning of trucks along an identical path. We classify different subproblems according to time windows and cost functions. A thorough analysis of computational complexity is provided. Our computational study identifies potential inefficiencies of the platoon formation process. Abstract: Platooning has been identified as a promising way to reduce the carbon footprint and fuel consumption of freight transportation. Recent technological developments connecting a platoon via digital data transmission even allow that the driver of the front truck controls all (unmanned) follower vehicles. Existing research mainly focuses on the technological and safety aspects of controlling the trucks and their distances. However, the efficiency of platooning is not only dependent on the aerodynamic drag, which considerably reduces with decreasing inter-vehicle distance; it is also influenced by the platoon formation process. To explore the impact of this and other neglected aspects on the efficiency of platooning (i.e., the diffusion of platooning technology, maximum platoon lengths, and the trucks' willingness-to-wait for partners) a basic scheduling problem for the platoon building process along a single path is investigated. By differentiating problem characteristics, e.g., the objective function, we derive different problem settings for which a detailed analysis of computational complexity is provided. Efficient algorithms are derived and applied to explore the impact of the diffusion of platooning technology, the maximum platoon length, and the tightness of time windows. Our results show that these factors can considerably reduce the positive effects of truck platooning, and, thus, the benefit may diminish.